Una breve sintesi sulla presenza degli anglicismi nel settore delle lingue speciali riguardo all ’italiano contemporaneo - Szpingier, Beata (Studia Romanica Posnaniensia, 2008)
This article presents the classification and description of borrowings from the English language in the sector of special languages with reference to contemporary Italian. The present times are characterized by multiplicity of linguistic variants. Different, ready-made solutions to are observed this complex situation.